Propagation of action potential activity in a predefined microtunnel neural network - Pan, Liangbin (2011)
A polydimethylsiloxane (PDMS) microtunnel device with two wells is aligned and attached on top of a multi-electrode-array (MEA). Neurons are grown first in one well and allowed to propagate axons through the tunnels into a second well. After ten days cells are plated in the second well, with much lower likelihood of extending axons back to the first well, with the intent of creating unidirectional connectivity between populations of neurons in the two wells. Here we report electrophysiological evidence that supports the hypothesis that the dominant information flow is in the desired direction. This was done by measuring the propagation speed and direction of individual action potentials, with the result that 84% of the spikes propagated in the desired direction. Further, we recorded globally synchronized burst activity on each of the electrodes, identified the timing of the first spike on each electrode, recorded locally synchronized burst activity which is found only in the second well and does not propagate back to the first well, and concluded that this measure of burst propagation supports the hypothesis of a unidirectionally connected network. Two hypotheses are discussed for mechanism underlying the activity pattern of the particular neural networks.